Penafsiran Nafsu Ammarah bi al-Suk Menurut Syeikh Mutawalli al-Sya’rawi (Menyoroti Siapa Musuh Paling Berbahaya Dalam Diri) - Yogi Imam Perdana (El-Afkar: Jurnal Pemikiran Keislaman dan Tafsir Hadis, 2019)
So far we always blame Satan in every sin that we repeatedly commit. But we realize that the temptation of Satan is very weak. Then why can people be so easily plunged into the abyss of sins many times. This question will be discussed thoroughly in the interpretation of Syeikh Mutawalli al-Sya'rāwi in his tafseer book. This research is a character study and manuscript study (tafseer), namely analyzing the texts related to this discussion, with the aim to explain, explain, and reveal the contents of the scriptures so that the message contained therein can be understood and practiced according to the figures studied. The results of this study found that it turns out that in us there is an enemy from within who has the biggest role in every sin committed, his name is nafs ammarah bi as-su͂k.